The Impact of Game-Based Learning on English Vocabulary Acquisition English Vocabulary Acquisition in Elementary School Students - Aisyahkila Nazwa Dalimunthe; Nadilla Indriani Nasution; Sindi Anzani; Siti Holijah (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
The purpose of this study is to see how game-based learning impacts primary school students' English vocabulary acquisition, where vocabulary acquisition is very important. The research method is qualitative. A qualitative approach is a research procedure that produces descriptive data on the behavior and written or spoken words of the research subjects. Qualitative research uses archival tools. The data results of this research are in the form of writings, descriptions, and explanations from books, journals, and articles related to the research problem. The results of the data analysis showed that using game-based learning resulted in a significant increase in English vocabulary. The findings suggest that this approach can be an effective approach to improving primary school students' English vocabulary comprehension. This study suggests that educators consider incorporating game-based learning into their curriculum.